Person-Organization Value Congruence: How Transformational Leaders Influence Work Group Effectiveness - Hoffman, Brian J.; Bynum, Bethany H.; Piccolo, Ronald F.; Sutton, Ashley W. (Academy of Management Journal, 2011)
Using multilevel structural equations modeling, we examine the extent to which the influence of transformational leadership on work group effectiveness flows through follower perceptions of person-organization or person-supervisor value congruence. Results indicate that the group-level effect of transformational leadership on work group effectiveness was fully accounted for by the group-level impact of transformational leadership on follower perceptions of person-organization value congruence, not by its impact on follower perceptions of person-supervisor value congruence. These results are discussed in the context of leadership as a “sense-making” process and the practical barriers faced by transformational leaders in modern organizations.